Syntax Dissipation of Language Acquisition in 4 Years Old Children: A Psycholinguistic Study - Bintari, Kartika; jatmika, D; Purnanto, Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Syntax Dissipation of Language Acquisition in 4 Years Old Children: A Psycholinguistic Study. The goal of this research is to describe the dissipation of subject, predicate, object, without dissipating the sentence who are spoken by the four years old children in the conversation topics that are given. This is a descriptive qualitative research with an object of syntax structure dissipation. The data for this research is in form of an utterance which contains syntax structure dissipation from the four years old children. The writer uses speaking method along with provoke technique, record technique, and conversation technique to acquire the data. The listening method also used to acquire original data. When analyzing the data, the writer uses match and distribute method. The distribution method is equipped with both replacement and modification method. In the four years old children’s utterance, the writer has found that in the simple sentence that they spoke there are, (1) the dissipation of subject, predicates, object, and without dissipation; (2) the type of simple sentence which has taken form in declarative, imperative, negative, and interrogative; (3) the word classes that appear in their utterance are verbs, adverbs, adjectives, nouns, and numbers; (4) class of phrases in a form of adjectives, nouns, numbers, and prepositional. In addition to simple sentence, there are also compound sentences that has (1) subject dissipation and without dissipation; (2) declarative sentence in a kind of sentence; (3) there are word class of verbs, nouns, and adjectives. The utterance of four years old children with incomplete syntax structure shows no significant problem dealing with their ability to deliver meaning. It happens because they are able to decide which diction they should use and which word that will be dissipated.